The role of interaction in online learning environments: students’ experiences and perspectives - da Silva, Rafael Leonardo; Gimenez, Telma Nunes (Revista Leitura, 2019)
This paper is situated in the research area of distance learning in virtual environments. This article analyses the views of Brazilian students on the interaction in an online course taught and tutored by pre-service teachers of Letras – Inglês from UEL in 2013. The data point to three perspectives: (i) interaction as a clarification tool for the content from the lessons and/or the required tasks in the course, (ii) interaction as a valuable tool for the social construction of knowledge, and (iii) interaction as a compulsory task. The analysis may contribute to further research in the online course research field. DOI: 10.28998/2317-9945.2014v1n53p235-262